Еndothelial dysfunction in patients with chronic obstructive pulmonary disease: feasibility of non-medicamental treatment (literature review and personal experience) - N. V. Vantiukh; O. I. Lemko (Zaporožskij Medicinskij Žurnal)
The aim of the work was to study the feasibility of the use of non-medicamental factors for the correction of endothelial dysfunction in patients with chronic obstructive pulmonary disease.